What Do Phonological Processing Errors Tell About Students' Skills in Reading, Writing, and Oral Language?. (February 2017) - Choi, Dowon; Hatcher, Ryan C.; Dulong-Langley, Susan; Liu, Xiaochen; Bray, Melissa A.; Courville, Troy; O'Brien, Rebecca; DeBiase, Emily
The kinds of errors that children and adolescents make on phonological processing tasks were studied with a large sample between ages 4 and 19 ( N = 3, 842) who were tested on the Kaufman Test of Educational Achievement–Third Edition (KTEA-3). Principal component analysis identified two phonological processing factors: Basic Phonological Awareness and Advanced Phonological Processing. Canonical analysis and correlation analysis were conducted to determine how each factor related to reading, writing, and oral language across the wide age range. Results of canonical correlation analysis indicated that the advanced error factor was more responsible for reading, writing, and oral language skills than the basic error factor. However, in the correlation analysis, both the basic and advanced factors related about equally to different aspects of achievement—including reading fluency and rapid naming—and there were few age differences.